Environmental responses to Holocene climate change, tephra deposition and land-use in Austur-Húnavatnssýsla - Tinganelli, Leone, 1964- (2017)
Despite the large number of Holocene palaeoenvironmental studies conducted in Iceland,few have attempted to provide a holistic approach to how climate, tephra deposition and land-use have combined to impact upon landscape stability and direct the Icelandic environment to its current state. Using sediments from three lakes, this study presents evidence of the effects of climate, volcanic and anthropogenic impacts on the environment in the highland margin, lowland and coastal areas in Austur-Húnavatnssýsla during the Holocene. Physical (magnetic susceptibility, dry bulk density, and sediment accumulation rate) and chemical proxies (organic matter, total nitrogen and carbon, C/N and C sequestration) are used as indictors of landscape (in)stability, and their relationships to climate change, land use, volcanology, and vegetation development and soil erosion are investigated. The results show that biological processes in the lakes have been primarily driven by the different geographical settings, landscape morphologies and vegetation covers in each area. The impacts of Holocene climate change on the environment were identified in all three lake records by distinct variations in both physical and chemical proxies. Welldeveloped vegetation cover is a highly important factor in diminishing the impact of heavy tephra fall on the environment. The lacustrine sedimentary records from Hafratjörn and Barðalækjartjörn highlight the important relationship between vegetation cover and landscape resilience to two of the most voluminous tephra deposits of the Holocene: Hekla 4 and Hekla 3. The detrimental human impact on landscape stability is marked in the lake records by an increase in minerogenic material and by elevated C/N ratios in the sediment. Landsvirkjun Energy Research Fund. The University of Iceland Research Fund. The Icelandic Research Fund (grant no. 141842-051)